2008
DOI: 10.1037/0735-7044.122.1.54
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of discrimination and reversal learning for olfactory and visual stimuli in aged rats.

Abstract: The present study investigated age-related differences in discrimination and reversal learning for olfactory and visual stimuli in 6 mo and 24 mo old rats. Rats were trained to discriminate between two pseudo-randomly selected odors or objects. Once each animal reached a criterion on discrimination trials, the reward contingencies were reversed. Young and aged rats acquired the olfactory and visual discrimination tasks at similar rates. However, on reversal trials, aged rats required significantly more trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 102 publications
(183 reference statements)
6
34
0
4
Order By: Relevance
“…Therefore, the rats in the present study showed significant memory impairments at 25-mo of age despite having longer average longevity than other strains of aged rats used in prior spatial exploratory studies [33]. The present finding is consistent with other studies that have reported age-related behavioral deficits in F344/BN rats 24–25-mo of age on various cognitive tasks [12,25,26,4042]. However, 24-mo-old F344/BN rats have been shown to match young rats on some behavioral measures such as trace and delayed eyeblink conditioning paradigms [43].…”
supporting
confidence: 91%
“…Therefore, the rats in the present study showed significant memory impairments at 25-mo of age despite having longer average longevity than other strains of aged rats used in prior spatial exploratory studies [33]. The present finding is consistent with other studies that have reported age-related behavioral deficits in F344/BN rats 24–25-mo of age on various cognitive tasks [12,25,26,4042]. However, 24-mo-old F344/BN rats have been shown to match young rats on some behavioral measures such as trace and delayed eyeblink conditioning paradigms [43].…”
supporting
confidence: 91%
“…This allows them to be more sensitive to reinforcement cues and reduce their reliance on using time as the main switching cue in MSR. That said, a reliable finding with T-maze procedures in rats is that of spontaneous alternation (Brushfield, Luu, Callahan, & Gilbert, 2008; Dudchenko, 2004). Rats tend not to repeat a previous response in spatially constructed apparatuses, such as the T-maze, Y-maze, and radial arm maze, even with lengthy delays between trials (Dudchenko, 2004; Evenden & Robbins, 1984).…”
Section: Control Of Switching Behavior By Reinforcement Cuesmentioning
confidence: 99%
“…The prefrontal cortex and OFC in particular has been implicated in aging related changes in decision-making in a variety of contexts (Rapp & Heindel, 1994; Zyzak et al ., 1995; Rypma & D’Esposito, 2000; Barense et al ., 2002; Lamar et al ., 2004; Smith et al ., 2004; Gazzaley et al ., 2005; Marschner et al ., 2005; Moore et al ., 2006; Brushfield et al ., 2008; Lasarge et al ., 2009; Mizoguchi et al ., 2009; Wang et al ., 2011). For example, aged rats are slower to acquire reversals, and these impairments have been linked to changes in processing in the OFC (Schoenbaum et al ., 2002; Schoenbaum et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%